Gadget bukan merupakan satu-satunya faktor yang mempengaruhi pola tidur pada remaja - Revina Ayu Lestari; Suryani Suryani; Agustina Rahmawati (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Adolescents are vulnerable to sleep disturbances due to biological changes during puberty and increasing exposure to digital devices. Gadget use is often associated with poor sleep patterns however, previous findings remain inconsistent, indicating that sleep problems among adolescents may be influenced by multiple factors. Purpose: To examine the relationship between gadget use and sleep patterns among seventh-grade students. Method: This study used a quantitative descriptive-correlational design with a cross-sectional approach. The sample consisted of 86 seventh-grade students selected using a purposive sampling method. Data were collected using the Smartphone Addiction Scale-Short Version (SAS-SV) to assess gadget use and the Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep patterns. Data analysis was performed using the Chi-Square test with a significance level of 0.05. Results: A total of 54.7% of students reported high levels of gadget use, while 91.9% reported poor sleep patterns. Statistical analysis showed no significant association between gadget use and sleep patterns (p = 0.352; OR = 0.454; 95% CI 0.083-2.481). Conclusion: Gadget use was not significantly associated with sleep patterns among seventh-grade students. Keywords: Adolescents; Gadget Use; Sleep Pattern; Smartphone, Students. Pendahuluan: Remaja rentan mengalami gangguan tidur akibat perubahan biologis selama masa pubertas dan paparan yang semakin meningkat terhadap perangkat digital. Penggunaan gadget sering dikaitkan dengan pola tidur yang buruk namun, temuan sebelumnya masih tidak konsisten, menunjukkan bahwa masalah tidur pada remaja mungkin dipengaruhi oleh berbagai faktor. Tujuan: Untuk mengkaji hubungan antara penggunaan gadget dan pola tidur di kalangan siswa kelas VII. Metode: Penelitian ini menggunakan desain deskriptif korelatif kuantitatif dengan pendekatan cross-sectional. Sampel terdiri dari 86 siswa kelas tujuh yang dipilih menggunakan metode sampling purposif. Data dikumpulkan menggunakan Skala Kecanduan Smartphone Versi Pendek (SAS-SV) untuk menilai penggunaan gadget dan Indeks Kualitas Tidur Pittsburgh (PSQI) untuk mengevaluasi pola tidur. Analisis data dilakukan menggunakan uji Chi-Square dengan tingkat signifikansi 0.05. Hasil: Sebanyak 54.7% siswa memiliki tingkat penggunaan gadget yang tinggi, sementara 91.9% mengalami pola tidur yang buruk. Analisis statistik menunjukkan tidak ada hubungan yang signifikan antara penggunaan gadget dan pola tidur (p = 0.352; OR = 0.454; 95% CI 0.083-2.481). Simpulan: Penggunaan gadget tidak secara signifikan terkait dengan pola tidur di kalangan siswa kelas VII. Kata Kunci: Penggunaan Gadget; Pola Tidur; Ponsel Pintar; Remaja; Siswa.